Pengaruh Corporate Social Responsibility Terhadap Kinerja Keuangan Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia periode 2008-2014 - Rilla Gantino (Accounting Departement Economics and Business Faculty Syiah Kuala University, 2016)
This study examine the influence of firm size, firm risk, capital intensity, leverage, tax, litigation, ownership structure, and growth opportunity for accounting conservatism.The study population was 129 manufacturing companies listed in Indonesian Stock Exchange between 2009 and 2011. Based on purposive sampling method, 38 manufaturing companies was selected (or 114 observations). Data was selected from the companies’ financial reports and analysed by using multiple linear regression. This study uncovered that. the firm size, firm risk, capital intensity, leverage, tax, litigation, ownership structure, and growth opportunity have influence for accounting conservatism collectively. But, only firm size, firm risk, capital intensity, ownership structure and growth opportunity affect accounting conservatism individually in the studied companies